Propagation prediction at 2 GHz band for fixed wireless access application ... [et al.] / [mikrofilem] - Hasnah Ahmad @ Abdullah; Mohamad Ghozali Hassan; Mohd. Fairul Effendi Mohd. Ali; Yusnizam Mohd. Yusoff; Zahari Jusoh (Skudai : Universiti Teknologi Malaysia, 1998)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1998